2010
DOI: 10.1007/s11144-010-0180-4
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline earth metal ion-exchanged β zeolite supported Pt catalysts for hydroisomerization of n-heptane

Abstract: Alkaline earth metal (Mg, Ca, Sr and Ba) ions were exchanged into Hb zeolite, which were used as the supports to load the noble metal Pt to prepare bifunctional catalysts for hydroisomerization of n-heptane. The catalysts were characterized by ICP, XRD, BET, NH 3 -TPD, H 2 -TPR and H 2 -chemisorption techniques, and evaluated in an atmospheric fixed bed reactor. The catalysts promoted by the alkaline earth metals are revealed to present much higher selectivity to isomerization than the counterpart Pt/Hb. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…The supports used for the bifunctional catalysts include SAPO (a kind of molecular sieves combined by Silicon, Aluminum, Phosphorus and Oxygen) [4,5], Y zeolite [6,7], β zeolite [8,9], SO 4 2− /ZrO 2 [10,11] and heteropolyacid [12,13], among which the three-dimensional 12-membered-ring β-zeolite is known as one of the most effective supports for hydroisomerisation of n-heptane. Chao et al [14] revealed that Pt-loaded β-zeolite showed higher selectivity to isomerisation and conversion than the one-dimensional 12-membered-ring mordenitesupported Pt catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The supports used for the bifunctional catalysts include SAPO (a kind of molecular sieves combined by Silicon, Aluminum, Phosphorus and Oxygen) [4,5], Y zeolite [6,7], β zeolite [8,9], SO 4 2− /ZrO 2 [10,11] and heteropolyacid [12,13], among which the three-dimensional 12-membered-ring β-zeolite is known as one of the most effective supports for hydroisomerisation of n-heptane. Chao et al [14] revealed that Pt-loaded β-zeolite showed higher selectivity to isomerisation and conversion than the one-dimensional 12-membered-ring mordenitesupported Pt catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al showed the increase in number of acid sites of Pt-H-Beta zeolites as Mg < Ca < Sr < Ba. Lack of agreement in acidity pattern reported in references 6 and 7 should be noticed [7]. Seddigi obtained decreased number of acid sites with higher acid strength (than that of zeolites HY) when the zeolites were modified with Ba [8].…”
Section: Introductionmentioning
confidence: 69%
“…In addition, Ca-Pt/deSi Beta was found to afford the highest isomer yields. Conversion sequence among these four metals was the same in the reaction of n-heptane isomerization reaction who reported Mg to yield the least acidic and Ba the highest acidic zeolites [7]. This suggested order may not be convincing while going down the Group from Mg to Ba, and basicity increases or acidity decreases making Mg most acidic.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on the above considerations, together with the fact that b zeolite is one of the most promising supports of the bifunctional catalysts for the hydroisomerization of n-heptane [18,19], it is adequate to attempt the composite molecular sieve b-MCM41 as the catalyst support, which has been seldom reported [20]. In this work, we synthesized b-MCM41 composite molecular sieves by a hydrothermal approach, and prepared Pt/b-MCM41 bifunctional catalysts for the hydroisomerization of n-heptane, observing a highly improved selectivity to isomerization with a considerably high conversion.…”
Section: Introductionmentioning
confidence: 99%